Writing successful grant proposals from the top down and bottom up - Sternberg, Robert J. (SAGE, 2014)
The chapter authors offer readers practical advice on planning, executing, submitting, and revising grant proposals in order to maximize their chances of success. Exploring both grant writers' and grant providers' perspectives, the text provides valuable insight into general strategies on how to write and submit proposals, as well as detailed information on the various types of proposals needed to reach particular research and teaching goals.